Advertising Slogan: History of Development in Print Media - Abisheva, V.T.; Murashova, D. (Ye.A.Buketov Karaganda State University Publishing house, 2013)
In article the interesting phenomenon in the modern advertizing text — a slogan is considered. Authors address to slogan history, its functioning in different conditions, to the factors forming his conceptual idea, receptions of submission of advertizing information. Slogans on a material of the Kazakhstan print media are analyzed. Authors define ways of development of an advertizing slogan, give the general scheme and slogan structure, note further evolution of a slogan.
Жарнамалық слоган: баспа БАҚ даму тарихы
Рекламный слоган: история развития в печатных СМИ
Keywords: slogan; advertising concept; advertising image; evolution of advertising slogan; History of Development; Print Media